Gastritis crónica y su relación con la enfermedad periodontal - Carrillo Moreno, Esteban Javier (2023)
ABSTRACT: Periodontal disease is a condition that involves several inflammatory conditions in the tissues supporting the teeth, starting with the biofilm, which considered as one of the extragastric reservoirs of Helicobacter pylori. This Gram-negative bacillus afflicts approximately 50% of the population worldwide, recognized by the WHO as a type 1 carcinogen, it designated as the main etiological agent of chronic gastritis. The present research was carried out with the objective of analyzing the relationship between chronic gastritis and periodontal disease, as well as to identify the sites of detection of HP in the oral cavity, to establish the elements that intervene in the development of this disease, its effects on health and to determine the dentist's work in this relationship. The research has been carried out by means of the bibliographic compilation of research through the systematic analysis of the literature in different scientific bases of impact such as Elsevier and mainly PubMed. In this descriptive type study, articles from 2013 to 2022 selected based on the selection criteria. Through the analysis, it determined that there is a relationship between both diseases, concluding that HP can be lodged in biofilm, saliva, among others, in addition to the fact that both diseases share the inflammatory state, which can intervene in their pathogenesis and that they need simultaneous treatment to avoid reinfections or exacerbations either in the gastrointestinal tract or in the supporting tissue of the teeth. Key words: Gastritis, Helicobacter pylori, Periodontal disease.